Welcome home. ([Australia] : [producer not identified], 1918)
Home made "Welcome home" three coloured banner printed on white textile. Features green border with text in red and blue. The Australian red ensign appears on a triangular "flag" in the top left corner, the union jack on a triangular "flag" in the top right corner.
Caption title.
National Library of Australia's copy slightly faded with some marking and small semi-threadbare areas, but in otherwise fair condition.
Also available online
Exhibited: "Keepsakes: Australians and the Great War", National Library of Australia, 26 November 2014 - 19 July 2015
Keywords: World War, 1914-1918 -- Veterans -- Australia -- Posters; World War, 1914-1918 -- Participation, Australian -- Posters; Banners -- Australia; War posters, Australian; War posters -- Australia; Australia -- Posters; Australian